CHANGES IN KNOWLEDGE AND BEHAVIOR OF POSYANDU CADRES THROUGH YOUTUBE EDUCATIONAL MEDIA INTERVENTION REGARDING STUNTING IN KARANG SATRIA VILLAGE, BEKASI REGENCY - Aulia Dahlan, Salsa (Kopertis Region IV Jabar and Banten, 2026)
Stunting is a chronic nutritional problem that affects children’s physical growth and cognitive development, and serves as an important indicator of public health status. Posyandu, as a community-based health service, plays a strategic role in preventing stunting, particularly through nutrition education and monitoring of child growth and development. This study aims to determine the changes in knowledge and behavior of Posyandu cadres after receiving educational interventions through YouTube videos in Karang Satria Village, Bekasi Regency. The study employed a quantitative approach using a one-group pretest–posttest design. The instruments used were questionnaires that measured the cadres’ knowledge and behavior before and after the intervention. The educational media consisted of YouTube videos containing information on the definition, causes, impacts, and prevention of stunting. Data were analyzed using the Wilcoxon Signed Rank Test. The findings showed a significant improvement in the cadres’ knowledge and behavior after the intervention (p < 0.05). These results confirm that YouTube is effective as an educational medium for enhancing the capacity of Posyandu cadres in stunting prevention efforts. Thus, YouTube-based interventions can serve as an innovative, accessible, and sustainable health education strategy, especially for rural communities